Root Damage under Alkaline Stress Is Associated with Reactive Oxygen Species Accumulation in Rice (Oryza sativa L.) - Zhang, Hui; Liu, Xiao-Long; Zhang, Rui-Xue; Yuan, Hai-Yan; Wang, Ming-Ming; Yang, Hao-Yu; Ma, Hong-Yuan; Liu, Duo; Jiang, Chang-Jie; Liang, Zheng-Wei (Frontiers in Plant Science, 2017)
Alkaline stress (high pH) severely damages root cells, and consequently, inhibits rice (Oryza sativa L.) seedling growth. In this study, we demonstrate the accumulation of reactive oxygen species (ROS) in root cells under alkaline stress. Seedlings of two rice cultivars with different alkaline tolerances, ‘Dongdao-4’ (moderately alkaline-tolerant) and ‘Jiudao-51’ (alkaline-sensitive), were subjected to alkaline stress simulated by 15 mM sodium carbonate (Na2CO3). Alkaline stress greatly reduced seedling survival rate, shoot and root growth, and root vigor. Moreover, severe root cell damage was observed under alkaline stress, as shown by increased membrane injury, malondialdehyde accumulation, and Evan’s Blue staining. The expression of the cell death-related genes OsKOD1, OsHsr203j, OsCP1, and OsNAC4 was consistently upregulated, while that of a cell death-suppressor gene, OsBI1, was downregulated. Analysis of the ROS contents revealed that alkaline stress induced a marked accumulation of superoxide anions (O2-) and hydrogen peroxide (H2O2) in rice roots. The application of procyanidins (a potent antioxidant) to rice seedlings 24 h prior to alkaline treatment significantly alleviated alkalinity-induced root damage and promoted seedling growth inhibition, which were concomitant with reduced ROS accumulation. These results suggest that root cell damage, and consequently growth inhibition, of rice seedlings under alkaline stress is closely associated with ROS accumulation. The antioxidant activity of superoxide dismutase, catalase, peroxidase, and ascorbate peroxidase increased under alkaline stress in the roots, probably in response to the cellular damage induced by oxidative stress. However, this response mechanism may be overwhelmed by the excess ROS accumulation observed under stress, resulting in oxidative damage to root cells. Our findings provide physiological insights into the molecular mechanisms of alkalinity-induced damage to root cells, and will contribute to the improvement of alkaline stress tolerance in rice plants.